2018
DOI: 10.1007/s00227-018-3362-7
|View full text |Cite
|
Sign up to set email alerts
|

Assimilation, translocation, and utilization of carbon between photosynthetic symbiotic dinoflagellates and their planktic foraminifera host

Abstract: Some species of planktic foraminifera inhabiting oligotrophic surface water environments are in an obligate symbiotic relationship with dinoflagellate microalgae, which can assimilate carbon (C) through photosynthesis. However, the mechanism and dynamics of C photosynthate translocation to the foraminiferal host, and related benefits for the dinoflagellates in this symbiotic association, are poorly constrained. As a consequence, the role of planktic foraminifera as autotroph organisms in ocean surface ecosyste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(64 citation statements)
references
References 58 publications
2
59
2
Order By: Relevance
“…In this diagram, the necessity of photosymbiosis, i.e., whether the relationship is essential for the host survival, is not considered since we cannot go into a detailed interactional relationship with our method. A recent study using a 13 C pulsechase experiment of O. universa, subsequent subcellular microimaging, and elemental analysis revealed the fate of assimilated carbon by the symbionts (LeKieffre et al, 2018). They showed a line of evidence of substance transfer from the symbionts to the host and their tight interrelationship.…”
Section: Characteristics and A New Framework Of Planktonic Foraminifementioning
confidence: 99%
See 1 more Smart Citation
“…In this diagram, the necessity of photosymbiosis, i.e., whether the relationship is essential for the host survival, is not considered since we cannot go into a detailed interactional relationship with our method. A recent study using a 13 C pulsechase experiment of O. universa, subsequent subcellular microimaging, and elemental analysis revealed the fate of assimilated carbon by the symbionts (LeKieffre et al, 2018). They showed a line of evidence of substance transfer from the symbionts to the host and their tight interrelationship.…”
Section: Characteristics and A New Framework Of Planktonic Foraminifementioning
confidence: 99%
“…Globigerinella siphonifera was divided Table S1 for detailed sampling information. Annual sea surface temperature (SST) data were from the World Ocean Atlas 2013 (Locarnini et al, 2013).…”
Section: Sampling and Identification Of Morphological Speciesmentioning
confidence: 99%
“…In return for metabolic ammonium and phosphate from the host, these symbionts photosynthesize and transfer a portion of the resulting organic matter to the foraminifer (Uhle et al, 1999), supplementing the organic carbon that it obtains from its largely carnivorous diet (Anderson et al, 1979;Spindler et al, 1984). These dinoflagellate-bearing foraminifera appear to depend on their photosymbionts for survival (i.e., "obligatory" symbiosis; Hemleben et al, 1989), such that they are functionally mixotrophic rather than heterotrophic (Le Kieffre et al, 2018;Stoecker et al, 2009;Stoecker et al, 2017). Some of these (sub)tropical foraminifer species (e.g., O. universa) also occur in the Subantarctic Zone (SAZ; between the Subantarctic Front, SAF, and the Subtropical Front, STF; King & Howard, 2003;Mortyn & Charles, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…NH þ 4 or NO 2À 3 ) is scarce and often limits biological productivity [4]. Bulk δ 15 N data from cultured foraminifera, measured after 15 N-spiked experiments, showed N-compound translocation from the endosymbionts to the foraminifera host cell [5]. When nitrate is not limiting in the environment, model calculations revealed that up to 57% of the foraminiferal N could be translocated from the symbionts, and even up to 90-100% for model calculations taking into account nitrogen uptake by the symbionts from the recycled ammonium pool.…”
Section: Introductionmentioning
confidence: 99%